The First World War and Indian Muslims - Singh, Rambha; Singh, Sunil Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The First World War’s eruption in 1914 sent ripples across the Indian subcontinent, deeply impacting its diverse communities—especially Indian Muslims, whose political and religious loyalties were put to an unprecedented test. At the outset, Muslims and Hindus alike rallied behind Britain’s war effort, hopeful that their allegiance might unlock long-promised political reforms. But that fragile unity faced a severe test when the Ottoman Empire—spiritually led by the Caliph, revered by many Sunni Muslims,sided with Britain’s enemies. For Indian Muslims, this sparked an intense internal conflict: Should they remain loyal to the colonial government or honor their faith-based connection to the Caliph? Many prominent Muslim leaders chose pragmatism, publicly backing Britain in hopes of protecting the broader interests of their community within the empire. Yet beneath the surface, deeper tensions stirred. Emotional ties to the Caliph, memories of previous colonial betrayals, the influence of Wahabi movements, and a wave of Turkish propaganda called for resistance, some even urging a jihad against British rule. Still, the majority of Indian Muslims stayed the course, reassured by British promises to protect Islamic holy sites and guided by the steady voices of elites and the Muslim press. However, a small but determined group took a different path. Viewing the global conflict as a chance for liberation, they forged clandestine alliances with Germany, Turkey, and Afghanistan, aiming to spark rebellion from within. Ultimately, the war exposed the layered and often conflicting identities Indian Muslims had to navigate between loyalty and dissent, faith and political ambition. Their responses revealed a deeply nuanced political awareness, setting the stage for the varied strategies they would later adopt in India’s struggle for independence.